2016
DOI: 10.1097/icu.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Blepharoptosis following ocular surgery

Abstract: Blepharoptosis is common following ocular surgery and can occur through multiple mechanisms. Certain individuals are at a higher risk for postoperative blepharoptosis, but all surgeons and patients undergoing ocular surgery should understand this risk when providing informed consent. Operative techniques can be adjusted to decrease rates of postoperative blepharoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…The risk of ptosis after any anterior segment surgery increases for many reasons, including older age, race, gender, operative time, type of anesthesia, eyelid edema, orbital inflammation, frequent use of topical steroid eye drops, anesthesia type (i.e., retrobulbar vs. topical), use of a lid speculum, use of a superior rectus bridle suture, and type of surgery. 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]38 Recent studies have shown less surgery-related ptosis, which likely reflects the use of more modern surgical techniques. 9,10 Consistent with previous studies, 9,10 a total 7 eyelids of 7 patients underwent PK in our study, but none of the patients underwent endothelial keratoplasty (EK).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of ptosis after any anterior segment surgery increases for many reasons, including older age, race, gender, operative time, type of anesthesia, eyelid edema, orbital inflammation, frequent use of topical steroid eye drops, anesthesia type (i.e., retrobulbar vs. topical), use of a lid speculum, use of a superior rectus bridle suture, and type of surgery. 7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]38 Recent studies have shown less surgery-related ptosis, which likely reflects the use of more modern surgical techniques. 9,10 Consistent with previous studies, 9,10 a total 7 eyelids of 7 patients underwent PK in our study, but none of the patients underwent endothelial keratoplasty (EK).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Most of the previous studies have reported eyelid ptosis following anterior segment surgery, and especially after cataract and glaucoma surgery. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] However, a few reports have appeared regarding ptosis correction surgeries in patients after keratoplasty. 6,7 For example, Michel et al 6 reported the use of Müller muscle-conjunctival resection (MMCR) without tarsectomy to treat ptosis in patients with a prior history of corneal surgery; however, they did not investigate the use of a bandage contact lens (BCL) after MMCR to protect the corneal grafts.…”
Section: Introductionmentioning
confidence: 99%
“…• Transient or persistent ptosis associated with a range of procedures, including glaucoma, cornea, strabismus, and cataract surgery [ 30 , 31 , 33 , 34 ]…”
Section: The Upper Eyelid and Causes Of Acquired Ptosismentioning
confidence: 99%
“…Reported rates of ptosis range from 1 to 44.4% and 0 to 12.9% among patients following extracapsular and phacoemulsification cataract surgery, respectively. Similarly, incidence after glaucoma surgery (7–19%) and vitreoretinal procedures (9.7–17%) appears to depend on the surgical technique used [ 31 ]. In glaucoma surgery, reported ptosis incidence is higher in trabeculectomy with mitomycin C (19% incidence) than when mitomycin is not used (12%) [ 31 ].…”
Section: Acquired Ptosis Risk Factorsmentioning
confidence: 99%
“…While the inciting stimulus is often involutional changes, certain insults can hasten this degenerative process. Intraocular surgery (eyelid speculum), frequent digital manipulation of the eyelids (allergies, blepharitis, compulsions, long-term contact lens use), and chronic eyelid inflammation have been shown to promote aponeurotic ptosis formation [9][10][11][12][13] . The levator function is often within the normal range (> 10 mm) even in the setting of moderate to severe ptosis.…”
Section: Aponeurotic Ptosismentioning
confidence: 99%